Level of Chemophobia and Relationship with Attitude towards Chemistry among Science Students - Noor Hidayah Binti Ibrahim; Zanaton Binti Hj. Iksan (Universitas Riau, 2018)
This study was conducted to investigate the level of chemophobia among science students and their attitude towards chemistry and their relationship. 101 Form 4 and Form 5 respondents were involved. Instrument used in this study was questionnaires comprises of three sections namely demographic background, level of chemophobia (chemistry learning anxiety, chemistry evaluation anxiety and chemicals handling anxiety) and attitude towards chemistry (enjoyment of learning chemistry, enjoyment of conducting laboratory activities, importance of chemistry in life and behavioral tendency to learn chemistry). Research findings showed that chemophobia among science students was at moderate level whereas students’ attitude towards chemistry was at high level. Research findings also showed that there was a moderate, negative significant relationship between the three factors of chemophobia with students’ attitude towards chemistry. Based on multiple regression analysis, there was a factor in chemophobia (chemistry evaluation anxiety) that showed significant influence with students’ attitude towards chemistry. This study implied that chemophobia among students should be overcome so that positive attitude towards chemistry could be instilled and hence, this would lead to the improvement in academic achievement and student’s participation in chemistry and science-related field.